Co3O4–C@FeMoP on nickel foam as bifunctional electrocatalytic electrode for high-performance alkaline water splitting. (21st September 2021) - Alhakemy, Ahmed Zaki; Senthilkumar, Nangan; Ding, Yichun; Li, Junwei; Wen, Zhenhai
Abstract: Exploring low-cost, highly efficient, and sustainable non-precious electrocatalysts for electrolytic H2 generation is driving research for the sustainable green urban development. Herein, we present a simple synthetic approach, through a two-step process, to prepare the bifunctional electrode of Co3 O4 –C@FeMoP hybrid micro rods/nanosheets anchored on nickel foam (NF), in which the Co3 O4 –C microrods grown on NF surface are decorated by FeMoP nanosheet layers, which is directly grown through a simple hydrothermal followed by post-phosphorization processes. The obtained hybrid hierarchical Co3 O4 –C@FeMoP/NF shows a significant enhancement in the electrocatalytic activities of oxygen/hydrogen evolution reactions (OER/HER) in comparison to the individual Co3 O4 –C and FeMoP nanostructures, thanks to more heterointerface active sites provided by FeMoP nanostructures with three-dimensional (3-D) layered architectures. The Co3 O4 –C@FeMoP/NF catalyst exhibits a relatively small overpotential of 200 mV vs. RHE for OER to achieve 20 mA/cm 2 and 123 mV vs RHE at 10 mA/cm 2 for HER along with excellent durability in alkaline electrolytes. We demonstrate the bifunctional electrocatalytic electrode as the electrolyzer for the generation of H2 via water splitting at small applied voltage of 1.61 V to achieve 10 mA/cm 2 and good stability for 24-h continuous running. Highlights: Synthesis of high-activity catalyst material Co3 O4 –C@FeMoP/NF. Decent electrocatalytic activity toward OER and HER in alkali. Alkaline water electrolysis system with bifunctional electrocatalyst electrode.